Diagnose Entwicklungsstörung Familiengeschichte - Familiendynamik - Professionelles Hilfesystem - Rosenthal, Gabriele; Witte, Nicole (Universitätsverlag Göttingen, 2021)
This empirical study reconstructs relations between the parents of children diagnosed as having special needs and professional members of the healthcare and help systems in Germany. The main focus is on interactions between the different groups of actors along the questions of how important these systems are for stimulating the children's development, and what role is played by the family history of the parents and the present situation of the families. Case examples are presented in this volume of five families with different family histories and different ethnic and religious belongings, and above all with different experiences of professional help.